Queijo colonial do Sudoeste do Paraná: da produção aos desafios para a formalização - Gheller, Diego Ghedini (2022)
Even with the changes brought about by the dominant agri-food system, traditional food products, especially artisanal cheeses, constitute an important strategy for the integration of family farmers into the local market, via short marketing circuits, with relationships of trust established between producers and consumers. However, the production and commercialization of colonial cheese, made from raw milk, has been taking place informally before the official health bodies, generating conflicts and institutional bottlenecks regarding regulatory frameworks and limiting the access of producers to better remunerating markets, even after significant advances have been made in the legislation that regulates its production. Therefore, this study aims to analyze legal, technical and socioeconomic factors that permeate this informality of colonial cheeses in Southwest Paraná. The research was carried out with cheesemakers and cheesemakers associated with the Associação dos Produtores de Queijo Artesanal do Sudoeste do Paraná – APROSUD, performing a qualitative analysis of the information and anchored by theories involving economic sociology. Among the factors that influence the permanence in informality or formalization are the future perspective in relation to their cheese production, the significance of income from cheese in relation to the income of the production unit, expectations regarding the construction of new markets, the external pressures exerted and the costs involved in complying with legal requirements. As for the application of current legislation, there is a lack of an approach that prioritizes the social and productive inclusion of small agro- industries, with actions that are primarily orientative and reasonable in terms of the demands imposed on farmers by the sanitary inspection agencies.